ASMA NADIA’s NOVEL SAKINAH BERSAMAMU APPRECIATION IN DISCUSSION CONTEXT STUDY - Annim Hasibuan (JOEL: Journal of Educational and Language Research, 2022)
The problem in this study is what is the context of the discourse contained in the novel Sakinah Bersamamu by Asma Nadia?. The purpose of this research is to describe the context of discourse in Asma Nadia's Sakinah Bersamamu novel. This research is focused on analyzing the discourse context in Asma Nadia's Sakinah Bersamamu novel. The population in this study is the novel "Sakinah Bersamamu" by Asma Nadia, which consists of 333 pages published by Asma Nadia Publishing in 2012. The sample in this study is the discourse in the novel Sakinah Bersamamu by Asma Nadia. The main research instrument in this study is researcher himself. Researchers play a full role in research activities from observing, recording, to analyzing data and describing it. The data analysis process begins by describing the data obtained in the field. Data obtained through reading novels. The results of this study conclude that the context of the discourse contained in the novel Sakinah Bersamamu by Asma Nadia is the physical context (topic of events, actors' actions, and the place of events), epistemic context, and social context.